2014
DOI: 10.3390/md12020601
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nuclear Receptors with Marine Natural Products

Abstract: Nuclear receptors (NRs) are important pharmaceutical targets because they are key regulators of many metabolic and inflammatory diseases, including diabetes, dyslipidemia, cirrhosis, and fibrosis. As ligands play a pivotal role in modulating nuclear receptor activity, the discovery of novel ligands for nuclear receptors represents an interesting and promising therapeutic approach. The search for novel NR agonists and antagonists with enhanced selectivities prompted the exploration of the extraordinary chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 225 publications
(231 reference statements)
0
26
0
Order By: Relevance
“…The results of the present study demonstrated that the three leads showed high bioactivity scores as KI, NRL and EIs (score>0.00) with Astragalin and Quercetin 7 being the most active as EIs (0.41 and 0.42, respectively) and Quercetin being the most active as KI and NRL (Table II). Nuclear receptors (NRs) are important pharmaceutical targets because they are key regulators of many metabolic and inflammatory diseases, including diabetes, dyslipidemia, cirrhosis and fibrosis (Yang, Li, Li, 2014). Based on our results, quercetin, qstragalin and quercetin 7 could be envisioned as potential ligands for NRs representing interesting and promising therapeutic alternatives to cure relevant disorders.…”
Section: Molecular Parametersmentioning
confidence: 99%
“…The results of the present study demonstrated that the three leads showed high bioactivity scores as KI, NRL and EIs (score>0.00) with Astragalin and Quercetin 7 being the most active as EIs (0.41 and 0.42, respectively) and Quercetin being the most active as KI and NRL (Table II). Nuclear receptors (NRs) are important pharmaceutical targets because they are key regulators of many metabolic and inflammatory diseases, including diabetes, dyslipidemia, cirrhosis and fibrosis (Yang, Li, Li, 2014). Based on our results, quercetin, qstragalin and quercetin 7 could be envisioned as potential ligands for NRs representing interesting and promising therapeutic alternatives to cure relevant disorders.…”
Section: Molecular Parametersmentioning
confidence: 99%
“…Several reviews concerning the sponge-derived bioactive marine alkaloids with future pharmaceutical applications have been published in the last decades [3, 26-31]. Sponges produce a plethora of chemical compounds with widely varying carbon skeletons.…”
Section: Introductionmentioning
confidence: 99%
“…The scores greater than 0.00 indicate high activity, between 0.00 to -0.5 indicate moderate activity and less than -0.5 indicate inactivity 27 . Nuclear receptors (NRs) are significant pharmaceutical targets, since, they are the main regulators of several metabolic and inflammatory diseases, including diabetes, dyslipidemia, cirrhosis and fibrosis 28 .…”
Section: Pdb 3e00 Is 29a Crystal Structure Of Methylisocitratelyase mentioning
confidence: 99%